2019
DOI: 10.1007/s40333-019-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity and moisture on the threshold shear velocity of saline sand in the Qarhan Desert, Qaidam Basin of China: A wind tunnel experiment

Abstract: Determination of the threshold shear velocity is essential for predicting sand transport, dust release and desertification. In this study, a wind tunnel experiment was conducted to evaluate the influence of salinity and moisture on the threshold shear velocity of saline sand. Saline sand samples (mean particle size of 164.50-186.08 μm and the total silt, clay and salt content of 0.80%-8.25%) were collected from three saline sand dunes (one barchan dune and two linear dunes) in the Qarhan Desert, Qaidam Basin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Consequently, plants are generally weaker in saline conditions and have smaller leaves than plants in non-saline and normal conditions. In most studies, such as Wang et al (2016) and Li et al (2019), desert salinity has reduced the EC of the soil; nonetheless, the results of the present study do not indicate this issue and are consistent with the results of studies by Rouhi Moghaddam et al (2018), Ladenburger (2006) and Feng et al (2018). The increase in salinity is mainly due to the increase in Na + and Clin the soil (Feng et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Consequently, plants are generally weaker in saline conditions and have smaller leaves than plants in non-saline and normal conditions. In most studies, such as Wang et al (2016) and Li et al (2019), desert salinity has reduced the EC of the soil; nonetheless, the results of the present study do not indicate this issue and are consistent with the results of studies by Rouhi Moghaddam et al (2018), Ladenburger (2006) and Feng et al (2018). The increase in salinity is mainly due to the increase in Na + and Clin the soil (Feng et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, the results have shown that the terrain sources have been located in the strongly saline (>10 3 mS/cm) terrain and consequently the sand dunes are also saline (>10 2 mS/cm). Also, research in the Qarhan Desert, China, showed that cohesion of saline sand when water was present increased the threshold shear velocity (Li et al 2019). Drying of Urmia Lake over the past decade has created new, salty terrains on the exposed bed allowing fine particles of salt to be carried by the wind causing the sand dunes to become salty.…”
Section: Discussionmentioning
confidence: 99%
“…The precipitation is mainly concentrated in May-September, which accounts for more than 80% of annual rainfall (Zhang et al, 2012). The soil type in the Qarhan Salt Lake is saline sand, with a mean particle size of 164.50-186.08 µm (Li et al, 2019b). The naturally dominant plants in the Qaidam Basin are shrub/semi-shrub desert vegetation, including Haloxylon ammodendron, Salsola spp., Ceratoides lateens, Ephedra przewalskii, Tamarix spp., Calligonum spp., Nitraria spp., and Artemisia spp.…”
Section: Study Areamentioning
confidence: 99%